Risk Management Analysis on the Achievement Of Performance Indicators - Nanik Dewi Setiawati; Siti Jahroh; Dominicus Savio Priyarsono (Eduvest - Journal of Universal Studies, 2025)
Control of non-communicable diseases, especially diabetes mellitus, is one of the priorities in public health programs. One of the performance indicators used to measure the success of this program is "Percentage of people with diabetes mellitus whose blood sugar is controlled at the Health Center/FKTP". The essence of this study is to find out the sources of risks that affect the achievement of these indicators, as well as analyze the causes and risk management efforts that occur in its implementation. This study uses a descriptive qualitative analysis method with a case study approach on the implementation of the diabetes mellitus program in the first level of health facilities. To identify the cause of risk, a cause and effect analysis method (fishbone diagram) is used which maps risk factors based on the categories of human resources, methods, materials, environment, measurement, technology, financing, and society.